Marker-Assisted Selection (MAS): untapped potential for enhancing food and nutrition securities in sub-Saharan Africa - Abdullahi, W.M.; Mu'az, S.A.; Togola, A.; Mohammed, G.S.; Umar, M.L.; Ongom, P.O.; Echekwu, C.; Boukar, O. (Springer, 2023)
Global food security has raised concerns for the rapidly growing population and extreme weather due to climate change. Conventional plant breeding deployed the current greatly fecund crops, but there must be an increase in the genetic improvement to meet the anticipated future demand. Existing crop breeding techniques and recent technologies could resourcefully be reconnoitered to increase crop improvement in the façade of increasingly perplexing production condition, which is discussed in this chapter. Agriculture is vital in securing millions of people in sub-Saharan Africa, as it has prodigious potential to contribute to the economic development of the region, livelihood improvement through income generation, and enhancing the potential of smallholder farmers and related value chains. Moreover, scientific innovations like MAS offer great potential to drive this envisioned change; decades have passed since this technology was first used in the world, but Africa as a continent with more genetic diversity of crops remains underrepresented. Here, we reviewed a purview on screening methods and patterns of how genetic diversity of available crops in the continent are exploited, since marker-assisted selection and its potential in tackling food and nutritional insecurity as well as climate change cannot be overemphasized. In this chapter, we highlighted potential for applying MAS in the genomic resources available in Africa. We explored the most important methods of plant breeding used with their advantages and limitations. Additionally, the quiescent and consequences for assimilation of hi-tech innovations in genetics and breeding are also explored. Since smallholder farmers are the major beneficiaries, we scrutinized how to guarantee steady and sustainable production of crops in sub-Saharan Africa, thereby producing climate-smart crops in this region.